Performance in Contemporary Art. - Wood, Catherine (London : Tate Publishing, 2018)
Ono, Yoko ; Rainer, Yvonne ; O'Grady, Lorraine ; Olowska, Paulina ; Hirata, Minoru ; Tanaka, Atsuno ; Burden, Chris ; Schneemann, Carolee ; Brus, Gunther ; Pane, Gina ; Export, valie ; Parente, Leticia ; Smith, Barbara, T. ; Smith, Jack ; Pier, Adrian ; IRWIN, ...
Overzicht geschiedenis van performance
boek